2013
DOI: 10.3748/wjg.v19.i44.8065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disease severity and necrosis on pancreatic dysfunction after acute pancreatitis

Abstract: Patients with SAP, NAP, pancreatic head necrosis and necrosectomy should be followed for pancreatic functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 17 publications
1
42
0
4
Order By: Relevance
“…5,22,23 The low incidence of pancreatic dysfunction in our study is probably related to the fact that only one patient developed necrotising AP, since that is a known risk factor for subsequent pancreatic dysfunction. 22,23 Pancreatogenic diabetes is in concordance with the definition by Ewald and Bretzal, 24 related to the presence of pancreatic exocrine insufficiency measured by FE; the present study only revealed a FE below the lower level of normal in two cases, neither of which were treated with antidiabetics, and which showed no evidence of prediabetes or diabetes in the obtained tests. The question is whether only patients with necrotising pancreatitis and subsequent chronic pancreatitis develop a significant loss of b-cell function and thus T3cDM (type 3c diabetes mellitus).…”
Section: Discussionmentioning
confidence: 74%
“…5,22,23 The low incidence of pancreatic dysfunction in our study is probably related to the fact that only one patient developed necrotising AP, since that is a known risk factor for subsequent pancreatic dysfunction. 22,23 Pancreatogenic diabetes is in concordance with the definition by Ewald and Bretzal, 24 related to the presence of pancreatic exocrine insufficiency measured by FE; the present study only revealed a FE below the lower level of normal in two cases, neither of which were treated with antidiabetics, and which showed no evidence of prediabetes or diabetes in the obtained tests. The question is whether only patients with necrotising pancreatitis and subsequent chronic pancreatitis develop a significant loss of b-cell function and thus T3cDM (type 3c diabetes mellitus).…”
Section: Discussionmentioning
confidence: 74%
“… 1 Additionally, severe acute pancreatitis has been known to cause an endocrine insufficiency over months, and whether this insulin-deficiency in combination with the glucose-dependent mechanisms of the human heart predispose TCM merits further investigation. 14 …”
Section: Discussionmentioning
confidence: 99%
“…The severity of AP was defined, based on the 2012 revision of the Atlanta classification and definitions by international consensus [ 15 ]. AP was subdivided into two types: interstitial edematous pancreatitis (AEP) and necrotising pancreatitis (ANP), in accordance with the appearance of CECT and the existence of pancreatic necrosis [ 17 ]. This clinical classification defined three degrees of severity: mild AP (MAP), moderately severe AP (MSAP), and severe AP (SAP).…”
Section: Methodsmentioning
confidence: 99%